Topical steroids as alternative to systemic hormonal treatment for inflammatory bowel diseases in pediatric practice - E. N. Fedulova; O. V. Shumilova; O. V. Fedorova; O. A. Tutina; G. V. Medyantseva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2011)
The aim of review. To share experience of application of topical steroids (Budenofalk®) in children with hormone – dependent inflammatory bowel diseases (IBD) and severe side effects on a background of systemic corticosteroids (CS).Original positions. Etiopathogenesis of IBD represents the cascade of self-maintaining pathophysiological reactions: adaptive microcirculational, hypoxicmetabolic, autoimmune inflammatory and dysbiotic disorders emerging on a background of genetic features of the body under the effect of unfavorable environmental factors. Anti-inflammatory treatment aimed to destruction of «vicious circle» of inflammatory responses occupies the main place in the treatment of IBD. CS are agents of choice of the second line. Prescription of CS is indicated at high severity of disease, active extraintestinal manifestations, absence of response to 5-aminosalicylic acid or dangerous side effects. At the same time CS application is associated to high risk of side effects and complications caused by their systemic action, and hormone-dependence. Introduction of topical steroids (Budenofalk®) to IBD treatment in some cases allows to resolve these problems. Experience of topical steroids application in the treatment of IBD in pediatrics is rather limited. On the basis of the Nizhny Novgorod scientific research institute of pediatric gastroenterology Budenofalk® was applied in 5 cases of IBD with severe cushingoid syndrome on a background of systemic CS and/or hormone-dependent course of disease to overcome dependency for CS and decrease of steroidrelated side effects. The article presents description of clinical case of successful application of budesonide according to determined goal.Conclusion. Budenofalk® can be a drug of choice in patients with hormone-dependent IBD, and at high risk of complications and severe side effects of systemic CS.